Fenótipos de dor no ombro de origem musculoesquelética: classificação e confiabilidade - Ribeiro, Gabriel Gaspar (Universidade Federal de São Carlos, 2024)
Shoulder pain is one of the musculoskeletal complaints with the highest incidence and treatment cost. Despite strong recommendations for conservative treatment, chronicity and recurrence of symptoms are frequent. When understood as a multidimensional and biopsychosocial phenomenon, shoulder pain condition reveals differently in clinical settings among people with similar complaints. These clinical differences might be related with predominant shoulder pain phenotype. Thus, identifying the predominant nociceptive, neuropathic or nociplastic shoulder pain phenotype can contribute to more accurate diagnoses and clinical decisions. Objective: This study aimed to classify the predominant pain phenotype in individuals with shoulder pain (ShoulderPhe) and identify the inter-rater reliability of the classification system for clinical use. Methods: The study included 108 individuals aged 18 to 60 years-old with primary musculoskeletal shoulder pain. The evaluation followed a comprehensive procedure based on the 7 steps of the 2021 International Association for the Study of Pain (IASP) classification system. Anamnesis and physical examination collected sociodemographic information, medical history, clinical data of the shoulder complaint, general health status, and sensory tests. Two raters independently classified the predominant shoulder pain phenotype for each individual using the IASP classification system adapted to shoulder pain. Agreement of each stage and for the final phenotype was analyzed using weighted kappa and prevalence-adjusted bias-adjusted kappa (PABAK) coefficients. Results: 76,6% of the participants were classified with nociceptive phenotype, 9,4% with neuropathic, and 14,0% with nociplastic. Inter-rater agreement was considered acceptable (PABAK > 0.4) for stages 1, 2, 4, 5, 6, 7, and the final phenotype, while stage 3 showed complete agreement (kappa = 1). Conclusion: The ShoulderPhe system was proved as a feasible tool for clinical use in individuals with shoulder pain with acceptable reliability. However, challenges remain in accurately identifying shoulder pain phenotypes, which indicates a need to refine the standardization of diagnostic criteria.
Phenotypes of shoulder pain of musculoskeletal origin: classification and reliability
Keywords: Musculoskeletal pain; Biopsychosocial; Physical therapy; Chronic pain; Guidelines; Dor musculoesquelética; Biopsicossocial; Fisioterapia; Dor crônica; Diretrizes; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL